Electronic media discourse about the 2017 referendum in the kurdistan region: the k24 website as a sample - Abdulkhalq Ibrahim Mstaffa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The study aims to identify the most important frameworks and topics used in the electronic media discourse during the media campaign for the 2017 referendum. This study is a descriptive study that uses a media survey method based on the content analysis. The electronic news websites represent the study community. The K24 website has selected as a sample of the study. (90) news stories were analyzed over the course of the campaign, which lasted for a month, among the most important findings of the study: that the discourse of the study sample was biased for the referendum, and that the frameworks most used in the study sample coverage of the campaign are the liability and conflict framework.